PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM DIMENSI LINGKUNGAN, KOMUNITAS, PASAR DAN TEMPAT KERJA PADA PERUSAHAAN PERUSAHAAN INDEKS LQ-45 YANG TERDAFTAR DI BEI TAHUN 2017-2019 - Cintya Trisanty; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
The aim of this study is to investigate disclosure of environmental, community, marketplace and workplace dimension of CSR on financial perfomance. The population in this study consists of all Indeks LQ-45  companies listed on Indonesia Stock Exchange (IDX) for the 2017-2019 period. Sample determined with purposive sampling method. Total sample of this research is 78 companies. The method of analysis in this study used multiple regression analysis. The results show that environmental and community dimension of CSR has positive impact to financial perfomance. Furthermore, we found no significant impact of marketplace and workplace dimension of CSR on financial perfomance.